Violence and aggression in psychiatric inpatient care in Sweden: a critical incident technique analysis of staff descriptions - Veikko Pelto-Piri; Lars-Erik Warg; Lars Kjellin (BMC, 2020)
Abstract Background Violence towards staff working in psychiatric inpatient care is a serious problem. The aim of the present study was to explore staff perspectives of serious violent incidents involving psychiatric inpatients through the following research questions: Which factors contributed to violent incidents, according to staff? How do staff describe their actions and experiences during and after violent incidents? Methods We collected data via a questionnaire with open-ended questions, and captured 283 incidents reported by 181 staff members from 10 inpatient psychiatric wards in four different regions. We used the Critical Incident Technique to analyse the material. Our structural analysis started by structuring extracts from the critical incidents into descriptions, which were grouped into three chronological units of analyses: before the incident, during the incident and after the incident. Thereafter, we categorised all descriptions into subcategories, categories and main areas. Results Staff members often attributed aggression and violence to internal patient factors rather than situational/relational or organisational factors. The descriptions of violent acts included verbal threats, serious assault and death threats. In addition to coercive measures and removal of patients from the ward, staff often dealt with these incidents using other active measures rather than passive defence or de-escalation. The main effects of violent incidents on staff were psychological and emotional. After violent incidents, staff had to continue caring for patients, and colleagues provided support. Support from managers was reported more rarely and staff expressed some dissatisfaction with the management. Conclusions As a primary prevention effort, it is important to raise awareness that external factors (organisational, situational and relational) are important causes of violence and may be easier to modify than internal patient factors. A secondary prevention approach could be to improve staff competence in the use of de-escalation techniques. An important tertiary prevention measure would be for management to follow up with staff regularly after violent incidents and to increase psychological support in such situations.